Reproduction and larval morphology af adenomera diptyx (anura: leptodactylidae) from the Argentinean humid Chaco an Brazilian Pantanal - Zaracho, Víctor Hugo (2017)
Fil: Zaracho, Víctor Hugo. Universidad Nacional del Nordeste, Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.